Temperature simulation of microwave ablation based on improved specific absorption rate method compared to phantom measurements. (31st October 2017) - Gao, Hongjian; Wu, Shuicai; Wang, Xiaoru; Hu, Rui; Zhou, Zhuhuang; Sun, Xuecong
Abstract: Purpose : To propose an improved specific absorption rate (SAR) computation method by incorporating a thermal conductivity item, develop mathematical simulation models based on the SAR, and enhance the accuracy of temperature simulation for 2450-MHz microwave fields. Materials and methods : Experimental data of 2450-MHz microwave antenna were obtained with a phantom and then new SAR equations were calculated according to Pennes bio-heat transfer equation. Next, the SAR equations were regarded as heating sources and SAR-derived temperature changes were simulated numerically; Finally, temperature measurement results were compared with simulation data to validate the accuracy of the new SAR method. Results : The simulated and measured temperature changes were generally in good agreement for the phantom. According to comparison results, the maximum error was less than 6 °C, the average error was less than 2 °C, and the standard deviation was less than 1 °C. Conclusions : This new SAR-derived simulation method can significantly simplify the simulation process and improve the prediction accuracy of microwave ablation temperature field.